Disorders of the Scapula and Their Role in Shoulder Injury : A Clinical Guide to Evaluation and Management - Kibler, W. Ben; Sciascia, Aaron D. (Springer International Publishing : Imprint: Springer, 2017)
This unique book - the first of its kind exclusive on disorders of the scapula - is a concise but comprehensive summary of the evidence that will enable clinicians to understand the scapula from its functions to its dysfunctions and includes clinical guidelines and pearls to improve the clinician's competencies for the treatment of shoulder disorders. Organized logically, the book opens with a review of the baseline mechanics and pathomechanics of the scapula, proceeds to evaluation, then describes in detail the association of the scapula with specific shoulder problems, including rotator cuff disease, labral injuries, glenohumeral and multidirectional instability, clavicle fractures, acromioclavicular joint separation, and shoulder arthrosis. Subsequent chapters cover scapular muscle detachment, neurological injuries and winging, scapular fractures and snapping scapula, in addition to basic and complex rehabilitation strategies. Each chapter includes a summary section with clinical pearls. In the past, in-depth research and expertise regarding the scapula was minimal, but a widening interest has resulted in a volume of literature that makes it possible and imperative that it be collected in a single volume. Disorders of the Scapula and Their Role in Shoulder Injury will be an excellent resource for orthopedic and trauma surgeons, residents and fellows.